Keeping the faith : Russian orthodox monasticism in the Soviet Union, 1917 1939 - Wynot, Jennifer Jean, 1971- (Eugenia and Hugh M. Stewart '26 series on Eastern Europe., 2004)
In Keeping the Faith, Jennifer Jean Wynot presents a clear and concise history of the trials and evolution of Russian Orthodox monasteries and convents and the important roles they have played in Russian culture, in both in the spiritual and political realms, from the abortive reforms of 1905 to the Stalinist purges of the 1930s. She shows how, throughout the Soviet period, Orthodox monks and nuns continued to provide spiritual strength to the people, in spite of severe persecution, and despite the ambivalent relationship the Russian state has had to the Russian church since the reign of Ivan the Terrible.Focusing her study on two provinces, Smolensk and Moscow, Wynot describes the Soviet oppression and the clandestine struggles of the monks and nuns to uphold the traditions of monasticism and Orthodoxy. Their success against heavy odds enabled them to provide a counterculture to the Soviet regime. Indeed, of all the pre-1917 institutions, the Orthodox Church proved the most resilient. Why and how it managed to persevere despite the enormous hostility against it is a topic that continues to fascinate both the general public and historians. Based on previously unavailable Russian archival sources as well as written memoirs and interviews with surviving monks and nuns, Wynot analyzes the monasteries? adaptation to the Bolshevik regime and she challenges standard Western assumptions that Communism effectively killed the Orthodox Church in Russia. She shows that in fact, the role of monks and nuns in Orthodox monasteries and convents is crucial, and they are largely responsible for the continuation of Orthodoxy in Russia following the Bolshevik revolution. Keeping the Faith offers a wealth of new information and a new perspective that will be of interest not only to students of Russian history and communism, but also to scholars interested in church-state relations.